Inheritance of black sigatoka disease resistance in plantainbanana (Musa spp.) hybrids - Ortíz, R.; Vuylsteke, D.R. (1994)
Black sigatoka (Mycosphaerella fijiensis Morelet), an airborne fungal leaf-spot disease, is a major constraint to plantain and banana (Musa spp.) production world-wide. Gaining further knowledge of the genetics of host-plant resistance will enhance the development of resistant cultivars, which is considered to be the most appropriate means to achieve stable production. Genetic analysis was conducted on 101 euploid (2x, 3x and 4x) progenies, obtained from crossing two susceptible triploid plantain cultivars with the resistant wild diploid banana 'Calcutta 4'. Segregating progenies, and a susceptible reference plantain cultivar, were evaluated over 2 consecutive years. Three distinct levels of host response to black sigatoka were defined as follows: susceptible (< 8 leaves without spots), less susceptible (8–10) and partially resistant (> 10). Segregation ratios for resistance at the 2x level fitted a genetic model having one major recessive resistance allele (bs1) and two independent alleles with additive effects (bsr2 and bsr3). A similar model explains the results at the 4x level assuming that the favourable resistance alleles have a dosage effect when four copies of them are present in their respective loci (bs i 4 ). The proposed model was further validated by segregation data of S1 progenies. Mechanisms of black sigatoka resistance are discussed in relation to the genetic model.